Low temperature CO oxidation over Ag/SBA-15 nanocomposites prepared via in-situ "pH-adjusting" method - Zhang, X.; Qu, Z.; Li, Xin Yong; Zhao, Q.; Wang, Y.; Quan, X. (2011)
The catalytic activity for CO oxidation over Ag/SBA-15 catalysts prepared by in-situ "pH-adjusting" method is studied in this paper. The prepared silver catalyst (7.8 wt%) under pH = 5 condition gives 98% of CO oxidation at 70 °C, as compared to 140°C with conventional silver catalyst without pH adjusting (6.1 wt%). However, more Ag2O clusters are formed inside the channels with the further pH increasing, resulting in the low catalytic activity for CO oxidation. Therefore the pH value shows significant effect on the silver content and the species state, consequently affecting the catalytic activity of Ag/SBA-15 catalysts for CO oxidation. © 2011 Elsevier B.V. All rights reserved.